Improving Athletes' Mental Health Through Self-Talk and Progressive Muscle Relaxation on the Performance of Aquatic Athletes at The Polaris Water Park Pool n Demak Regency - Sungkowo, Sungkowo; Sobihin, Sobihin; UN, Rizam Ahada; Wicaksono, Anggit; Sungatno, Sungatno; Azizah, Ifa Nurul; Latif, Abdul; Fadillah, Imron (Jurnal Abdimas, 2025)
Tension and stress during competition often lead to changes in psychological functioning, such as reduced concentration, loss of focus, increased anxiety, or, from a somatic perspective, increased muscle tension. Mental health can be affected by tension, which is seen as a result of physical interactions. Self-talk is a "strategy" employed by every athlete, whether verbalized or simply thought. Muscle tension is generally associated with stress, anxiety, and fear, as part of a process that helps our bodies prepare for potentially dangerous situations. The methods used included psychological education on self-talk and progressive muscle relaxation, progressive muscle relaxation practice, discussions, mentoring, and data collection on the athletes' mental health. The results of the community service research, as shown in the table, categorize 11 swimmers based on their mental health: 6 athletes categorized as moderate, and 5 athletes as low. Athletes with moderate mental health are considered to have good emotional, psychological, and social well-being, which influences how a person thinks, feels, and acts, including their ability to cope with the pressures of competition. Conversely, athletes with low mental health are classified as having good mental health.